Numerical Analysis of the Thermophysical Properties of R600a Refrigerant Enhanced with Diamond Nanoparticles in Vapour Compression Refrigerating System - Odunfa, K.M; Ajuka L.O; Odeniyi, S.O (International Journal of Engineering and Management Research, 2022)
Addition of nanoparticles to lubricants and refrigerants in vapour compression refrigerating systems has been a subject of consideration for engineers and researchers worldwide due to its heat transfer enhancement properties coupled with power consumption reduction capacity. Nanolubricants and nanorefrigerants are forms of nanofluids which possess better heat transfer performance than pure lubricants and refrigerants. For performance analysis to be carried out, basic thermophysical properties of nanolubricant and nanorefrigerant such as density, heat capacity and thermal conductivity must be calculated and analysed. In this paper, a computer application was developed based on several derived numerical equations to calculate the density, heat capacity and thermal conductivity of diamond/mineral oil nanolubricant and diamond/mineral oil/R600a nanorefrigerant. This study showed that the thermal conductivities at various diamond nanoparticle volume fractions are higher than pure lubricant and refrigerant. The densities of the nanolubricant and nanorefrigerant were lower than that of the pure lubricant and refrigerant. However, the heat capacities decreased with increase in nanoparticle volume fractions and these were found to be less than that of pure lubricant and refrigerant. The study therefore established that heat transfer performances increase with thermal conductivity and heat capacity while pumping power increases with enhanced density. Hence, the addition of diamond nanoparticles to mineral oil and R600a refrigerant improves performance of system.